PATHOGENIC AND MORPHOLOGICAL VARIABILITY IN COLLETOTRICHUM CAPSICI ISOLATES CAUSING ANTHRACNOSE OF CHILLI (CAPSICUM ANNUM L.) - NEERAJ SINGH TANWAR; R. N. BUNKER; JITENDRA KUMAR; POONAM SHREE (The Bioscan, 2015)
Pathogenic and morphological variability among 4 isolates of anthracnose of chilli (Colletotrichum capsici) from four states-Rajasthan, Gujarat, Karnataka and Madhya Pradesh were studied. Pathogenic variability was studied in micro plots grown 5 different cultivars. Among the isolates, the maximum colony diameter after 7 days was (88 mm) in UDR Cc-01, it produced maximum number of spore (21.0 x 10 4 conidia/mm 2 medium). The maximum size of conidia was the isolate GUJ Cc-03 which measured 22.6 (20.3–24.8) x 3.7 (3.3–4.1) μm, maximum size of setae was the isolate BAN Cc-02 which measured 110.3 (98.1-123.5) × 4.8 (4.2-5.3) and maximum size of accervulus was the isolate UDR Cc-01 which measured 200.8 (178.7-224.8) μm in vitro study. In field, the evaluation was done to find out the resistant chilli cultivar and pathogenic potential of different isolates. Isolate UDR Cc-01 caused shortest latent period (48 hrs) in Pusa jwala and longest latent period of 80 hrs in Sadabahar. UDR Cc-01 was the most virulent, as it caused susceptible (S) reaction (disease score 5.5 and PDI 61.2) on Pusa jwala cultivar and moderate susceptible (MS) reaction with score 4.5 and PDI 50.2 in California wonder and disease score 3.7 with 41.3 PDI in Yellow type.